(-3) divided by (3/4) x (2/7) x (-5/16) divided by (5/7) = ?

13 answers

To solve this problem, we need to follow the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, Addition and Subtraction from left to right).

First, let's simplify the expression within the parentheses:
(-3) ÷ (3/4) × (2/7) × (-5/16) ÷ (5/7)

We can simplify each fraction separately:

(-3) ÷ (3/4) = -3 × (4/3) = -12/3 = -4

(2/7) × (-5/16) = (2 × -5)/(7 × 16) = -10/112 = -5/56

Now, we can rewrite the expression with the simplified fractions:

-4 × (-5/56) ÷ (5/7)

Next, let's divide the fractions:

-4 × (-5/56) ÷ (5/7) = (-4 × -5)/(56 × 5/7) = 20/(280/7) = 20 × (7/280) = 140/280 = 1/2

Therefore, the simplified expression is 1/2.
(8/9) x (-3/4) divided by (1/9) x (-4/5) divided b (3/5) = ?
To solve this problem, we need to follow the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, Addition and Subtraction from left to right).

Let's simplify the expression step by step:

(8/9) × (-3/4) ÷ (1/9) × (-4/5) ÷ (3/5)

First, let's simplify the multiplication of the fractions:

(8/9) × (-3/4) = -24/36 = -2/3

Next, let's simplify the division of the fractions:

(-2/3) ÷ (1/9) = (-2/3) × (9/1) = -18/3 = -6

Now, let's simplify the other division:

(-6) ÷ (-4/5) = (-6) × (-5/4) = 30/4 = 15/2

Finally, let's simplify the last division:

(15/2) ÷ (3/5) = (15/2) × (5/3) = 75/6 = 25/2

Therefore, the simplified expression is 25/2.
(-3/5) x (5/16) x (7/12) divided by (-3/16) x (-5/7) =
To solve this problem, we need to follow the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, Addition and Subtraction from left to right).

Let's simplify the expression step by step:

(-3/5) x (5/16) x (7/12) ÷ (-3/16) x (-5/7)

First, let's simplify the multiplication of the fractions:

(-3/5) x (5/16) x (7/12) = (-3 x 5 x 7) / (5 x 16 x 12) = -105 / 960

Next, let's simplify the division of the fractions:

(-105/960) ÷ (-3/16) = (-105/960) x (16/(-3)) = -16,800 / -2,880

Finally, let's simplify the other division:

(-16,800 / -2,880) ÷ (-5/7) = (-16,800 / -2,880) x (7/(-5)) = 235,200 / 40,320

Therefore, the simplified expression is 235,200 / 40,320, which cannot be reduced any further.
what is the answer to that in decimal form?
To find the decimal form of the expression, we can divide the numerator (235,200) by the denominator (40,320).

235,200 ÷ 40,320 = 5.83125

Therefore, the decimal form of the expression is approximately 5.83125.
how many ounces are in 1/2 of 1/5 of a 10-ounce block of cheese?(1 point)
To find the number of ounces in 1/2 of 1/5 of a 10-ounce block of cheese, we need to multiply the different fractions together.

(1/2) × (1/5) × 10

First, let's simplify the fractions:

(1/2) × (1/5) = 1/10

Now, let's multiply the simplified fractions by 10:

(1/10) × 10 = 1

Therefore, there are 1 ounce in 1/2 of 1/5 of a 10-ounce block of cheese.
a group of 9 people won 1/5 of a $4,500 prize. how much money did each person in the group win?(1 point)
To find out how much money each person in the group won, we need to divide the total prize amount by the number of people in the group.

The group of 9 people won 1/5 of a $4,500 prize.

First, let's find out how much the group won:

1/5 of $4,500 = $4,500 ÷ 5 = $900

Now, let's divide the total prize amount by the number of people in the group:

$900 ÷ 9 = $100

Therefore, each person in the group won $100.
(-2) x (1/5) divided by (2/3) x (-5/6) divided by (3/4)
To solve this problem, we need to follow the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, Addition and Subtraction from left to right).

Let's simplify the expression step by step:

(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)

Let's start with the multiplication and division of the fractions:

(-2) × (1/5) = -2/5

(2/3) × (-5/6) = (2 × -5) / (3 × 6) = -10/18 = -5/9

Now, let's simplify the other division:

(-2/5) ÷ (-5/9) = (-2/5) × (-9/5) = 18/25

Finally, let's divide by 3/4:

(18/25) ÷ (3/4) = (18/25) × (4/3) = 72/75

To simplify the fraction 72/75, we can divide both the numerator and denominator by their greatest common divisor, which is 3:

72 ÷ 3 / 75 ÷ 3 = 24/25

Therefore, the simplified expression is 24/25.